Germinated Thai Black Rice Extract Protects Experimental Diabetic Rats from Oxidative Stress and Other Diabetes-Related Consequences - Chaiyavat Chaiyasut; Bhagavathi Sundaram Sivamaruthi; Noppawat Pengkumsri; Waranya Keapai; Periyanaina Kesika; Manee Saelee; Parichart Tojing; Sasithorn Sirilun; Khontaros Chaiyasut; Sartjin Peerajan; Narissara Lailerd (MDPI AG, 2016)
Background: Diabetes mellitus (DM), particularly type 2 DM (T2DM), is one of the most common metabolic disorder worldwide. The prevention measures and treatment strategies for DM are improving steadily. The current study explains the impact of germination on phytochemical content of Thai black rice (BR), and the influence of germinated BR extract (GBRE) supplementation on diabetic conditions in rats. Methods: BR was germinated and the phenolic, anthocyanin, and γ-aminobutyric acid (GABA) content of the extract were analyzed using HPLC and spectrophotometric methods. Streptozotocin-induced diabetic rats were supplemented with high and low doses of GBRE. The plasma glucose, insulin, cholesterol, triglyceride levels, antioxidant status, and antioxidant enzyme levels of treated animals were assessed using ELISA and spectrophotometric methods. Results: Germination enhanced the GABA content of BR, and GBRE intervention improved the total antioxidant capacity and antioxidant enzymes levels in diabetic rats. The plasma glucose, cholesterol, triglyceride levels, insulin resistance and glucose tolerance were reduced, and the degree of insulin secretion in rat plasma was significantly increased upon GBRE treatment. Both pre and post-treatment approaches showed the anti-diabetic ability of GBRE. In most of the analyzed parameters, GBRE was quite equal to the performance of drug-metformin. Conclusions: GBRE supplementation helps prevent and manage the consequences of DM.